"قياس أثر محددات الرضا الوظيفي على الولاء التنظيمي" (دراسة ميدانية على شركات القطاع العام والخاص العاملة في مجال صناعة الرخام وأحجار الزينة في محافظة اللاذقية) - ديب, كندة علي; تركمان, حنان; داؤد, علا محسن (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يركز البحث بشكل أساسي على قياس أثر محددات الرضا الوظيفي على الولاء التنظيمي للعاملين في شركات القطاع العام العاملة في مجال صناعة الرخام وأحجار الزينة ومقارنتها مع مثيلاتها من شركات القطاع الخاص, وتقديم المقترحات اللازمة لرفع مستوى الولاء التنظيمي للعاملين في الشركات محل الدراسة من خلال تحقيق الرضا الوظيفي لهم باعتباره أحد الوسائل الهامة التي تمكن الإدارة من تحقيق ولاء العاملين وبالتالي تحسين أداء الموارد البشرية واستثمارها بالشكل الأمثل لتحقيق الأهداف التي تسعى إليها إدارة هذه المنظمات. وفي هذا الإطار يتناول البحث مفهوم الرضا الوظيفي, والعناصر التي تساهم في تحقيقه, وعلاقة الرضا الوظيفي ببعض المتغيرات التنظيمية. كما يركز البحث على موضوع الولاء التنظيمي وعلاقته ببعض المتغيرات التنظيمية. تمهيدا لزيادة الولاء التنظيمي للعاملين وتحسينها. إضافة إلى دراسة عملية تم وفقها تحليل الاستبيان الموزع والتوصل إلى مجموعة من النتائج كان من أهمها أن الأجر أهم محددات الرضا الوظيفي تأثيرا على الولاء التنظيمي ثم طبيعة وظروف العمل المادية, فرص الترقية, وأخيرا علاقات العمل السائدة, وتم تقديم عدد من المقترحات التي تساهم في تحقيق أهداف البحث. The research concentrates mainly on the standard of the effect of the elements on the job satisfaction on the organizational commitment for workers in public companies in the field of making marble and decoration stones and comparing them with those in the particular companies and presenting the necessary suggestion to increase the level of organizational commitment through achieving the job satisfaction for workers. This is because it is considered one of the most important ways which enables the administration to achieve allegiance for its workers. This leads to improving the performance of the human resources and using them in the best way to fulfill the aims which these organizations work for. In this field, the research dealt with the idea of the job satisfaction and its elements which contribute in achieving it. It also studied the relationship between the job satisfaction and some of the organization varieties. The research also concentrated on the idea of the organizational commitment and the relationship between the organizational commitment and some of the organization varieties to increase the organizational commitment. In addition, a practical study was performed according to which an analysis of the distributed survey has been carried out, leading to a number of results. One of the most important results which is that the pay is the most effective job satisfaction index on organization loyalty, then comes the nature of the work and its physical conditions, chances for promotion, and finally the prevailing work relationships. Finally, a number of suggestions have been proposed that may contribute to achieving the goals of the study.